The Aristocratic Culture of Great Britain in the Globalization Era - T. A. Ivushkina (Vestnik MGIMO-Universiteta)
In the focus of the article are the culture and the language of the British aristocracy in the period of globalization covering the last four decades. Informational technologies and American mass culture they have brought about have a tremendous influence on the style of life of the class under consideration. The Internet and television have become the most powerful means of breaking traditions and causing changes in all spheres.